Minimizing the Adverse Impacts of Soil Salinity on Maize and Tomato Growth and Productivity through the Application of Plant Growth-Promoting Rhizobacteria - Hiba Yahyaoui; Nadia El Allaoui; Aziz Aziz; Majida Hafidi; Khaoula Habbadi (Crops)
Soil salinity significantly impacts crop productivity. In response, plant growth-promoting rhizobacteria (PGPR) offer an innovative and eco-friendly solution to mitigate salinity stress. However, research on PGPR’s effects on crop physiology under varying salinity levels is still emerging. This study evaluates the impact of five bacterial strains, isolated from compost, on the growth of maize (Zea mays) and tomato (Solanum lycopersicum) plants under different levels of salt stress. This study involved treating maize and tomato seeds with five bacterial strains, and then planting them in a greenhouse under varying salt stress conditions (43 mM, 86 mM, 172 mM, 207 mM NaCl) using a Randomized Complete Block Design. Results showed that bacterial inoculation improved plant growth under saline conditions. S2015-1, S2026-2, and S2027-2 (Bacillus cereus, Acinetobacter calcoaceticus, Bacillus subtilis) were particularly effective in promoting plant growth under salt stress, especially at ionic concentrations of 43 mM and 86 mM, leading to a substantial increase in fresh and dry weight, with strain S2015-1 boosting chlorophyll by 29% at 86 mM in both crops. These results highlight the potential of PGPR to enhance crop resilience and productivity under salinity stress, promoting climate-smart agricultural practices.